Pendampingan Pembuatan Label Dan Banner Sebagai Upaya Strategi Pemasaran Produk UMKM Cenil Mbok Mini - Zenita Afifah Fitriyani; Diego Ahmad Dandy; Dony Prasetyo; Dwi Indasari; Eko Nurfiansyah; Erlin Ananda Putri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Cenil or Cetil is a traditional food or snack made from a mixture of starch and granulated sugar, colored, shaped into small balls, eaten with grated coconut. Cenil is a traditional Javanese snack, especially in the East Java area. Cenil mbok mini was founded in 1967 and is still active until now in 2023, so for around 56 years cenil mbok mini has become one of the culinary mainstays of Mojowiryo village, Kemlagi subdistrict, Mojokerto regency. Cenil is neatly packaged and increasingly modern in terms of packaging and manufacturing methods. This Community Service aims to introduce traditional food to the community, as well as to preserve traditional food so that it does not become extinct. The method used in this training is Preparation Step, Implementation Step, and Evaluation Step. As a result of this dedication, traditional snacks have labels to be marketed. Marketing strategies can help improve MSMEs.